Analyze The Strength and Weaknesses of “The Killers” Written By Ernest Hemingway - Stefani, Angela; Tuminah, Tuminah (Journal of Mandalika Social Science, 2024)
Based on the short story The Killers by Ernest Hemingway. This research aims to find out the characters and characterizations in the short story The Killers. And knowing the relationship between characters and characterizations and the strengths and weaknesses of the short story “The Killers”. This research is a descriptive qualitative research whose data source is the short story The Killers. The data collection technique is done with the simak technique by observing and taking notes on the dialog used by each character of the short story to determine the characterization of each character. The data collected is analyzed by approaching Edgar V. Robert's theory to analyze the character and characterization in the short story The Killers through what the character says about himself, what the character himself does, what other characters say about the analyzed character, and what the author says about the analyzed character. The results of this study show that the main character has 7 characters with different characters and characteristics. There are 3 types of characters in it, namely protagonists, antagonists, and tritagonists. These characters show themselves through the dialog used by each character. The contribution shown by the researcher is that this research can help in finding the strengths and weaknesses of the short story The Killers through characters and characterizations, to provide recommendations to readers to be selective in choosing age-appropriate reading.